2015
DOI: 10.1016/j.biortech.2015.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the hydrolysis and methane production potential of mixed food waste by an effective enzymatic pretreatment

Abstract: In this study, a fungal mash rich in hydrolytic enzymes was produced by solid state fermentation (SSF) of waste cake in a simple and efficient manner and was further applied for high-efficiency hydrolysis of mixed food wastes (FW). The enzymatic pretreatment of FW with this fungal mash resulted in 89.1 g/L glucose, 2.4 g/L free amino nitrogen, 165 g/L soluble chemical oxygen demand (SCOD) and 64% reduction in volatile solids within 24h. The biomethane yield and production rate from FW pretreated with the funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Bread is an ideal substrate for solid state fermentation, and we have previously shown that a portion of the waste bread can be used as a substrate for the production of a multi-enzyme solution, rich in glucoamylase and protease, using Aspergillus awamori solid state fermentation (Melikoglu et al, 2013b). The global market for feed enzymes is a major industry and the global market size and it was estimated to reach $727 million in 2015(Li et al, 2012, and amongst different enzymes, glucoamylase and protease is crucially important for the conversion of food wastes that are rich in protein and starch into nutrient rich monomers for the production of value added products. Recently, other researcher also showed that different types of food Page 5 of 45 A c c e p t e d M a n u s c r i p t 5 waste can be used as novel approaches for the production of glucoamylase and protease using A. awamori and A. oryzae (Sun et al, 2014;Uckun Kiran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bread is an ideal substrate for solid state fermentation, and we have previously shown that a portion of the waste bread can be used as a substrate for the production of a multi-enzyme solution, rich in glucoamylase and protease, using Aspergillus awamori solid state fermentation (Melikoglu et al, 2013b). The global market for feed enzymes is a major industry and the global market size and it was estimated to reach $727 million in 2015(Li et al, 2012, and amongst different enzymes, glucoamylase and protease is crucially important for the conversion of food wastes that are rich in protein and starch into nutrient rich monomers for the production of value added products. Recently, other researcher also showed that different types of food Page 5 of 45 A c c e p t e d M a n u s c r i p t 5 waste can be used as novel approaches for the production of glucoamylase and protease using A. awamori and A. oryzae (Sun et al, 2014;Uckun Kiran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The global market for feed enzymes is a major industry and the global market size and it was estimated to reach $727 million in 2015(Li et al, 2012, and amongst different enzymes, glucoamylase and protease is crucially important for the conversion of food wastes that are rich in protein and starch into nutrient rich monomers for the production of value added products. Recently, other researcher also showed that different types of food Page 5 of 45 A c c e p t e d M a n u s c r i p t 5 waste can be used as novel approaches for the production of glucoamylase and protease using A. awamori and A. oryzae (Sun et al, 2014;Uckun Kiran et al, 2015). The effects of fermentation time, initial moisture content, and particle size on glucoamylase and protease production were previously optimised under static air in petri dishes following a stepwise optimisation strategy as shown in Figure 1 (Melikoglu et al, 2013c;Wang et al, 2009;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An efficient pretreatment process to stabilize the feedstock is necessary before hydrogen and methane fermentation. Various pretreatment strategies for FW prior to anaerobic digestion/fermentation have been reported, namely enzymatic treatment [64], thermal treatment [65,66], acid [67], alkali [68,69], ozone [66], hydrothermal [70], autoclaving [71], bio-electrohydrolysis [72], and ultrasonication [73]. All these pretreatments either lead to hydrolysis of the FW, or enrichment of hydrogen/methane producers and inhibition of the pathogenic bacteria in the FW.…”
Section: Bioenergy Production Divisionmentioning
confidence: 99%
“…Obviously, high-concentration of glucose favors the subsequent bioethanol production. It should be realized that commercial enzymes are costly and generally available in a single-type form [5]. In order to make the enzymatic hydrolysis of FW more cost-effective, the enzymes should be produced in situ from a cheap feedstock without complex and costly downstream separation and purification.…”
Section: Introductionmentioning
confidence: 99%